Isolation and Screening of Microbes for Poultry Probiotics and Their Growth on Different Sugar Resources - Tresnawati Purwadaria; I Putu Kompiang; Jinadasa Darma; Supriati .; Emi Sudjatmika (Jurnal Ilmu Ternak dan Veteriner, 2003)
The microorganism used as probiotics must be bio-safety, could be cheaply and easily produced, and suitable with the environment of the digestive track. Isolation was carried out from commercial culture (containing mixture of Bacillus spp.), digestive tract (proventriculus, small intestine and large intestine) of local and broiler chickens, and commercial yoghurts (fermented milk). Neutral and acidic nutrient agars (NA) were used as the media at room temperature and in the aerobic or anaerobic conditions. Separate colonies were isolated, stained with Gram and spore staining and observed under the microscope. The bacteria which were Gram positive bacillus and can form spores were further identified. Eight different species of Bacillus spp.: B. laterosporus, B. coagulans, B. alvei, B. circulans, B. brevis B. bodius, B. pasteurii, and B. macrolides were isolated from the commercial mixture. From the digestive tracts of local and broiler chickens, 13 bacteria and 2 yeasts were isolated, while 5 yeast were obtained from two commercial yoghurts. Those bacteria were facultative aerobic and only grew in neutral condition and not in acidic condition (pH 4.5), while the yeast were either facultative anaerobic also can grow in pH neutral and 4.5. The ability of each isolates to grow in the media containing mixture of minerals and glucose, sucrose or molasses were evaluated. Incubation was carried out in the shaker incubator at 40° C, 150 rpm for 48 hours. Dry matter of the biomass was determined as the growth parameter. All isolates of bacteria and yeast can grow in the substrate containing glucose, sucrose and molasses. Variance analyses show that there were interactions between kind of bacteria and carbon source or between kind of yeast and carbon source (P<0.05). Three isolates of bacteria that had highest production of biomass were B. coagulans on sucrose (the third for molasses), Sp. 9 on glucose, and B. apiaries on sucrose (the sixth on molasses). B. apiaries isolated from digestive tract of local chicken will be useful to be developed as probiotics. The highest production of yeast was the control Saccharomyces cerevisiae on three sugars. Between the isolates from digestive tract of local chicken, Toluraspora delbrueckii AL-15 produced 13.8x10-1 mg/ml biomassa on molasses.